A guerra espiritual em voto: a circulação de sentidos no acontecimento #bolsonarosatanista nas eleições presidenciais de 2022 - Mathias, Maria Eduarda (2024)
Platformization, as outlined by Van Dijck et al. (2018), describes a phase in our connected society where digital platforms deeply infiltrate social structures, impacting institutions, economic transactions, cultural and social practices, and thus perpetuating existing social frameworks. Moreover, with ongoing mediatization, we observe social media platforms increasingly shaping a continuous exchange of meanings and responses within society. This constant flow of communication animates narrative passages, contributing to the formation of a social response system that reacts to and engages with circulating messages and events (Braga, 2017a). Against this backdrop, we delve into the intricate interplay between politics, religion, and the ramifications of communicational and social shifts, examining the use of networks and their role in misinformation; the ascent of conservatism and the discourse surrounding spiritual warfare (Guadalupe;Grundberger, 2019), metaphorically tied to ultra politics and its impact on Brazilian democracy. By adopting França and Lopes' (2017) methodological approach to event individualization, we investigate the emergence of the #bolsonarosatanista phenomenon on Twitter (X) during the second round of the 2022 Brazilian presidential elections. Employing Braga's (2017a, 2017b) framework of meaning circulation and forward flow, we analyze the contestation of religious meanings associated with the hashtag, uncovering the instrumentalization of faith and a fusion of political and religious discourses. We discern the unfolding and appropriation of religious agendas in electoral contexts, spotlighting the influence of conservative and evangelical factions in politics and the subversion of conventional religious narratives.